A COMPREHENSIVE REVIEW OF DESIGN EDUCATION FOR SUSTAINABLE DEVELOPMENT - Bachate, Ravindra; Patel, Maulik; Satyavada, Rahul; Shende, Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper provides an in-depth analysis of the recent upsurge of interest in incorporating sustainability into design education, recognizing its pivotal role in addressing urgent global challenges. By thoroughly examining existing academic literature, design curriculum, and successful case studies of sustainable design initiatives, it offers a comprehensive overview of the current state of design education for sustainable development. Furthermore, this study explores innovative pedagogical methods and successful tactics for integrating sustainability principles into design education. It also critically evaluates potential challenges and obstacles faced in this endeavor, offering insights into overcoming them. Through this comprehensive analysis, the paper aims to contribute to the advancement of design education for sustainability by providing a nuanced understanding of the current research landscape. By highlighting successful approaches and innovative strategies, this paper seeks to inspire educators and institutions to further integrate sustainability into their design curricula. Ultimately, this research endeavours to foster a more sustainable design practice by equipping future designers with the necessary knowledge, skills, and mindset to address complex environmental and social challenges